203k views
2 votes
Which of these shows the result of using the first equation to substitute for Y in the second equation, then combining like terms?

Which of these shows the result of using the first equation to substitute for Y in-example-1
User Mnille
by
6.3k points

1 Answer

4 votes

Answer:

Option D

Explanation:

Equations given in the question are y = 2x and 2x + 3y = 16

As per question we replace y = 2x in the second equation and combination the like terms.

2x + 3(2x) = 16

2x + 6x = 16

8x = 16

Option D will be the answer.

User Kevthanewversi
by
5.6k points